Socio-Technical Architecture of Garden Lamps Based on Symbolic Values of Bola Soba Roofs in Bone Regency, Indonesia - Haedar, Ahmad Wahidiyat; Aliah, Nurul; Iriandy, Iriandy (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2025)
The socio-technical architecture of garden lamps based on symbolic values of the “Bola Soba” roof (Bugis Bone traditional house) is an edu-tourism attraction for all of us. The socio-technical system is an old approach that was created in the development of integrated tourism components based on local cultural values. The results of qualitative research using the Research & Development Method and phenomenological approach explain the noumena (meaning) behind the phenomenon (fact) of the socio-technical architecture of garden lamps based on the symbolic value of the Bola Soba roof. The results of the study found that the architectural work of garden lamps in Bone Regency based on the symbolic value of the Bola Soba roof is very full of philosophical meaning as educational tourism learning. The actualization of basic values and value orientations as noumena behind the phenomenon of socio-technical architecture based on symbolic values is identical to the upper part of the garden lamp in the form of the roof of the Bugis Bone traditional house, namely Bola Soba. The use of the Bola Soba roof shape on garden lamps is not only aesthetic but also a symbol of preserving local Bugis culture (ethics), as well as a historical and educational marker to remind the public of the cultural values of ancestral heritage (kinesthetics). Likewise, the center of the garden lamp is in the form of a line ornament with a philosophical word motif as a typical motto of the Bugis Bone community culture, namely